DUAL-PURPOSE ASSESSMENT FOR SWEETPOTATO - Lestari, Sri Umi; Hapsari, Ricky Indri (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2015)
This study aimed to classify the types of sweet potato based on the ratio of total dry matter of roots to vine (R/V) in order to make the option available in integrating the crop-livestock systems. Seventeen sweet potato cultivars were planted in Randomized Complete Block Design with three replications applied at two locations, Malang and Blitar. Each cultivar planted in plot measures 2.5 m x 5 m in Malang and 3.0 m x 5 m in Blitar, and each consists of four rows with a spacing of 25 cm in rows. All cultivars gave a dose of 250 kg NPK fertilizer (15-15-15)/ha twice, one-third of dose given at planting and the remainder in a month after planting. Plants were harvested at four months after planting. Fresh weight and dry weight of storage root, fresh weight and dry weight of vines, harvest index, and the ratio R/V are determined.Â There was different performance of 17 cultivars planted at two locations. Cultivars planted in Malang were classified into four types, namely forage, which consists of three cultivars among 17 cultivars, low dual-purpose (3 cultivars), high dual-purpose (7 cultivars), and low root production (4 cultivars); while cultivars planted in Blitar turned into the forage type.Â Keywords: dual-purpose, root/vine ratio, sweet potato